(untitled) (Eurasian Research Bulletin, 2022)
The article determined the energy consumption of the body of student athletes, based on how many times a week they go in for sports, taking into account some anthropometric indicators. There was a correlation between their basal metabolic rate and the energy they expend during exercise. In addition, energy costs were calculated when a student ran a distance of 100 m, depending on the speed and weight of the girls. Based on the results obtained, appropriate conclusions were drawn